Boron carbide / regenerated cellulose composite fiber prepared based on copper ammonia method and processing method thereof
The preparation of boron carbide/regenerated cellulose composite fibers by cupr ammonia method has solved the problems of poor environmental protection and insufficient breathability of traditional boron-containing fibers, and achieved excellent environmental protection performance and good breathability.
Patent Information
- Application Number
- CN202510611511.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-13
- Publication Date
- 2025-06-13
AI Technical Summary
Traditional boron-containing fibers have shortcomings in environmental protection and breathability. The use of a large number of chemical reagents during the preparation process leads to environmental pollution, and the fibers are difficult to degrade and breathable.
Boron carbide/regenerated cellulose composite fibers are prepared by cupric ammonia method. Through the tight composite structure of regenerated cellulose and boron carbide particles, combined with the cupric ammonia method process, the production of chemical pollutants is reduced and the air permeable channel inside the fiber is formed.
The generation of chemical pollutants is significantly reduced, and a breathable channel is formed inside the fibers, which solves the problems of poor environmental protection and insufficient air permeability of traditional boron-containing fibers. It has the advantages of excellent environmental protection performance and good air permeability.
Smart Images

Figure CN120138825A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fiber material preparation. Specifically, it relates to a boron carbide / regenerated cellulose composite fiber prepared by the cuprammonium method and its processing method. Background Art
[0002] Boron-containing fibers have important application values in the field of neutron shielding due to their excellent neutron absorption performance. Boron element, especially boron-10 isotope, has an extremely high absorption cross-section for neutrons, and can effectively absorb neutrons, thereby reducing the intensity of neutron radiation. By uniformly distributing boron elements in the fiber matrix, boron-containing fibers can significantly improve the neutron shielding performance of materials. In addition, boron-containing fibers also have the characteristics of light weight and high strength, which enables them to provide efficient and economical solutions in occasions where neutron shielding is required, such as the nuclear industry, medical equipment, and scientific research experiments. Common boron-containing fibers include boric acid ester polyethylene nanofibers, boron carbide-reinforced polyethylene fibers, glass fiber / boron carbide / epoxy resin composites, etc.
[0003] Traditional boron-containing fibers have obvious deficiencies in terms of environmental protection and air permeability. A large amount of chemical reagents are used in the preparation process of many boron-containing fibers, and these reagents may release harmful gases during production, causing environmental pollution. These fibers are difficult to degrade after use, and will cause long-term pollution to the soil and water bodies. Due to the relatively thick boron carbide layer on the fiber surface, the air permeability and water permeability of the fibers are poor, which limits their use in some applications that require good air permeability.
[0004] In view of the above problems, the existing technology urgently needs to be improved. Summary of the Invention
[0005] The purpose of the present invention is to provide a boron carbide / regenerated cellulose composite fiber prepared by the cuprammonium method and its processing method, which has the advantages of excellent environmental protection performance and good air permeability.
[0006] The technical solution adopted by the present invention to solve its technical problems is as follows: A boron carbide / regenerated cellulose composite fiber prepared by the cuprammonium method, the technical solution is as follows: The boron carbide / regenerated cellulose composite fiber is mainly composed of regenerated cellulose and boron carbide, and the cellulose and boron carbide particles are closely intertwined.
[0007] The present invention also proposes a method for preparing boron carbide / regenerated cellulose composite fibers by the cuprammonium method, including the following steps: (1) Cuprammonium solution (or cuprammonium ethylenediamine solution) and plant fiber are mixed according to the mass ratio of copper element / cellulose = 0.2 - 0.4, and stirred to fully dissolve the solid. Then citric acid with a mass fraction of 5% of copper ions is added, and filtered through a polypropylene filter screen with an average pore size of about 1 - 20 μm to obtain cuprammonium pulp. Boron carbide powder is added to the cuprammonium pulp and fully mixed to form a boron carbide / cuprammonium pulp mixture. Ultrasonic degassing is used to remove as many internal bubbles as possible to obtain a boron carbide / cellulose spinning solution. (2) The spinning solution is added to a micro-injection pump. The injection pump is started, and the spinning solution is extruded through a spinneret into a coagulation bath for rapid wire drawing and solidification molding. The fiber is wound after passing through the coagulation bath, the second bath, and the washing bath. After oiling, drying, and finishing, the boron carbide / cellulose composite fiber is obtained.
[0008] Further, the particle size of the boron carbide powder is ≤20 μm, and the preferred particle size range is 2 - 0.5 μm.
[0009] Further, the ultrasonic degassing is carried out using an ultrasonic generator with a frequency range of 20 - 40 kHz, and the treatment time is not less than 10 minutes.
[0010] Further, the concentration of copper element in the cuprammonium solution is 0.5 - 2 mol / L.
[0011] Further, the plant fiber includes but is not limited to cotton linter, softwood pulp, hardwood pulp, and hemp waste.
[0012] The beneficial effects of the present invention are as follows: A boron carbide / regenerated cellulose composite fiber prepared based on the cuprammonium method and its processing method provided by the present invention, through the tight composite structure of regenerated cellulose and boron carbide particles, combined with the cuprammonium method process, significantly reduces the generation of chemical pollutants. At the same time, air-permeable channels are formed inside the fiber, effectively solving the problems of poor environmental protection and insufficient air permeability of traditional boron-containing fibers. It has the advantages of excellent environmental protection performance and good air permeability. The boron carbide loading is high, it has good mechanical properties, and the preparation process is simple and the cost is low, which is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 It is the process flow chart of the present invention.
[0014] Figure 2 It is the macroscopic and microscopic morphology comparison diagram of the boron carbide / regenerated cellulose composite fiber (not oiled), Among them: a, b, c - are regenerated cellulose fibers with a boron carbide addition amount of 0; d, e, f - are boron carbide / regenerated cellulose composite fibers with a boron carbide addition amount of 0.1 (w / w); g, h, i—the boron carbide / regenerated cellulose composite fiber with a boron carbide addition of 0.3 (w / w).
[0015] Figure 3 It is a comparative diagram of EDS (B, C, O, N) elemental analysis of the boron carbide / regenerated cellulose composite fiber (not oiled). Among them: a—is the EDS elemental analysis of the regenerated cellulose fiber with a boron carbide addition of 0; b—is the EDS elemental analysis of the boron carbide / regenerated cellulose composite fiber with a boron carbide addition of 0.1 (w / w); c—is the EDS elemental analysis of the boron carbide / regenerated cellulose composite fiber with a boron carbide addition of 0.3 (w / w).
[0016] Figure 4 Comparative XRD analysis diagram of the boron carbide / regenerated cellulose composite fiber (not oiled). Among them: Curves a, b, c, and d are respectively boron carbide powder raw material, boron carbide / regenerated cellulose composite fibers with boron carbide additions of 0, 0.1, and 0.3 (w / w). Specific implementation manners
[0017] The present invention will be further described below in conjunction with the accompanying drawings and specific implementation manners.
[0018] In the prior art, boron-containing fibers are widely used in the nuclear industry due to their excellent neutron absorption performance. Traditional boron-containing fibers mostly use non-degradable materials such as polyethylene and epoxy resin as the substrate, and a large amount of chemical reagents are used in the production process, posing a risk of environmental pollution. The too-thick boron carbide layer on the fiber surface leads to insufficient air permeability, restricting its application in scenarios such as medical protection and filtration materials. For example, the protective clothing for nuclear power plant operators needs to meet both neutron shielding and air permeability requirements, but traditional fibers are difficult to balance both.
[0019] To solve the above problems, the inventor found that the non-degradability of the fiber matrix material is the core factor leading to environmental pollution. By analyzing the degradable characteristics of cellulose, an attempt was made to composite boron carbide with regenerated cellulose. It was found in the experiment that the fiber structure formed by simple mechanical mixing is loose and the boron carbide particles are easy to fall off. After multiple experimental verifications, the copper ammonia method was used to dissolve cellulose to form a uniform matrix, which can achieve the tight binding of boron carbide and cellulose molecular chains.
[0020] Therefore, the present invention proposes a fiber structure formed by the composite of boron carbide and regenerated cellulose, and the two components are composite in a tightly intertwined manner.
[0021] Among them, regenerated cellulose refers to a cellulose material formed by chemically dissolving plant fibers and then remolding. Specifically, it can be formed by dissolving cotton linter pulp by the cuprammonium method and then regenerating. Its three-dimensional network structure provides a bearing space for boron carbide particles and endows the fiber with degradability.
[0022] Among them, closely intertwined refers to an interpenetrating structure formed by boron carbide particles being embedded in the gaps between cellulose molecular chains. Specifically, it can be achieved by ultrasonic dispersion to uniformly distribute boron carbide in the cellulose solution and then solidifying and molding. This structure avoids the local aggregation of boron carbide to form a dense layer and maintains the pore connectivity inside the fiber.
[0023] Specifically, a porous network is formed during the solidification process of the regenerated cellulose solution, and boron carbide particles are entangled and fixed by cellulose molecular chains. When the cuprammonium solution dissolves plant fibers, the original crystalline regions are destroyed, and the recombined amorphous regions are more likely to wrap boron carbide particles. During solidification and molding, the capillary force generated by the contraction of cellulose molecular chains causes physical bonding at the interface between boron carbide and cellulose. The microporous channels retained inside the fiber allow gas molecules to diffuse, and at the same time, the intertwined cellulose chains prevent the migration and shedding of boron carbide particles.
[0024] Compared with the prior art, traditional boron-containing fibers use thermoplastic polymers as the matrix and need to be processed by high-temperature melting, while this solution uses a room-temperature wet spinning process to avoid the oxidation of boron carbide caused by high temperature. In the prior art, boron carbide is attached to the fiber surface as a coating to form a continuous dense layer, while in this solution, boron carbide is uniformly dispersed in the cellulose matrix, which not only ensures the neutron shielding efficiency but also maintains the air permeability porosity of the fiber.
[0025] Through the above technical solutions, the present invention realizes the degradability of the boron-containing fiber matrix, and after being discarded, it can be decomposed into carbon dioxide and water by microorganisms. The multi-level pore structure inside the fiber enables the water vapor transmission rate to reach more than 90% of that of conventional cellulose fibers, meeting the ergonomic wearing requirements while maintaining the neutron shielding performance.
[0026] The present invention further provides a processing method for preparing boron carbide / regenerated cellulose composite fibers by the cuprammonium method, including the following steps: (1) A cuprammonium solution (or cuproethylenediamine solution) and plant fibers are mixed according to a mass ratio of copper element / cellulose = 0.2 - 0.4, and then stirred to fully dissolve the solid. 5% citric acid with respect to the mass fraction of copper ions is added, and filtered through a polypropylene filter screen with an average pore diameter of about 1 - 20 μm to obtain cuprammonium pulp. Boron carbide powder is added to the cuprammonium pulp and fully mixed to form a boron carbide / cuprammonium pulp mixture. Ultrasonic degassing is used to remove as many internal bubbles as possible to obtain a boron carbide / cellulose spinning solution; (2)The spinning solution is added to a micro-injection pump. The injection pump is turned on, and the spinning solution is extruded through a spinneret into a coagulation bath, where it is rapidly drawn and solidified into a fiber. The fiber is wound after passing through the coagulation bath, the second bath, and the washing bath. After oiling, drying, and finishing, the boron carbide / cellulose composite fiber is obtained.
[0027] Among them, the mass ratio of copper element / cellulose is 0.2 - 0.4, and this ratio range can balance the dissolution efficiency of cellulose and the stability of the spinning solution. The addition amount of citric acid is based on the mass fraction of copper ions, for example, controlled at about 5%. Its function is to adjust the pH value of the solution and inhibit the aggregation of copper ions. The pore size range of the polypropylene filter screen is 1 - 20 microns, which can effectively intercept undissolved fiber impurities. The ultrasonic degassing treatment promotes the bubbles to escape from the mixture through high-frequency vibration, avoiding the generation of structural defects inside the fiber. The multi-stage bath treatment includes a coagulation bath, a second bath, and a washing bath, which respectively undertake the functions of fiber forming, removal of residual solvents, and impurity cleaning.
[0028] Specifically, after the cuprammonium solution is mixed with plant fibers, copper ions form stable complexes with cellulose molecular chains, forming a uniform pulp system. The addition of citric acid not only neutralizes the alkaline environment but also prevents metal aggregation through the coordination of carboxyl groups with copper ions. The filtration step removes undissolved plant fiber fragments and impurities through a polypropylene filter screen with a controllable pore size to ensure the purity of the spinning solution. During the dispersion process of boron carbide powder, the ultrasonic cavitation effect can break the particle aggregates and make them evenly distributed in the cellulose matrix. In the spinning stage, the micro-injection pump precisely controls the flow rate of the spinning solution and forms a continuous fiber bundle in cooperation with the spinneret. The multi-stage bath treatment makes the cellulose molecular chains arrange orderly and form a porous structure through the gradual replacement of different solvents, while eluting the residual copper ions and dispersants.
[0029] Compared with the prior art, traditional boron-containing fibers are mostly prepared using polyethylene or epoxy resin as the matrix, which requires the use of organic solvents and is difficult to degrade. This method uses renewable plant fibers as raw materials and realizes the low-temperature dissolution of cellulose through the cuprammonium method, avoiding high-temperature degradation and the use of toxic reagents. In the traditional process, boron carbide particles are prone to sedimentation during the melt extrusion process, while in this method, through ultrasonic dispersion and solution spinning processes, the particles are stably suspended and evenly compounded. In the prior art, the dense boron carbide layer formed on the fiber surface hinders gas permeation, while the porous structure formed in this method maintains the fiber breathability while retaining the dispersion of boron carbide.
[0030] Through the above technical solutions, the present invention solves the problems of serious chemical pollution and poor fiber air permeability in traditional processes. The degradable characteristics of the cellulose matrix reduce the environmental harm of waste. The ultrasonic dispersion and solution spinning processes achieve high-load and uniform composite of boron carbide, and the porous structure maintains the original air and water permeability of the fiber. The effective removal of copper ions during the fiber forming process avoids the influence of metal residues on the material properties, and the multi-stage bath treatment ensures a dense fiber structure and stable mechanical properties.
[0031] The present invention further proposes that the particle size of the boron carbide powder does not exceed 20 microns, and the preferred particle size range is from 2 microns to 0.5 microns.
[0032] Among them, the particle size of the boron carbide powder refers to the maximum lateral dimension of the particles in the dispersion system, and can be specifically measured by a laser particle size analyzer or a scanning electron microscope. Powders with the required particle size range are obtained by mechanical grinding or chemical synthesis methods. Controlling the upper limit of the particle size can avoid the settlement or agglomeration of particles due to gravity in the spinning solution. The preferred particle size range further balances the particle specific surface area and suspension stability, while ensuring uniform dispersion and avoiding too high viscosity of the spinning solution.
[0033] Specifically, boron carbide particles with a particle size not exceeding 20 microns form a stable colloidal dispersion system in the cuprammonium spinning solution. Ultrasonic degassing and mechanical stirring are used to make the particles fully contact with the cellulose molecular chains. During the stretching process in the coagulation bath, small-sized particles can be embedded in the gaps of the cellulose network rather than aggregating on the fiber surface, thus forming a uniform composite material structure. The preferred particle size range of 2 microns to 0.5 microns significantly increases the particle specific surface area, enhances the interfacial binding force with cellulose, and at the same time avoids irreversible agglomeration of nanoscale particles due to van der Waals forces, maintaining the rheological properties of the spinning solution to meet the requirements of continuous spinning.
[0034] Compared with the prior art, existing boron-containing fibers mostly use micron-sized or even millimeter-sized boron carbide particles, resulting in an island-like distribution of particles inside the fiber, forming local stress concentration points and hindering gas permeation. By limiting the particle size range, the present invention enables the particles to be continuously and gradiently distributed on the fiber cross-section, effectively increasing the neutron absorption path length at the same boron content and reducing the blockage of pores inside the fiber.
[0035] Through the above technical solutions, the present invention solves the problems of decreased fiber air permeability and fluctuating shielding efficiency caused by uneven dispersion of boron carbide particles, avoids the abnormal increase in the viscosity of the spinning solution and the clogging of the spinneret caused by ultrafine particles, and improves the stability of the neutron shielding performance of the composite fiber while maintaining the processing efficiency.
[0036] The present invention further proposes that the plant fibers include cotton linter, softwood pulp, hardwood pulp, and ramie waste.
[0037] Among them, cotton linter refers to the short fiber residues generated during the cotton processing process, which can be specifically realized by the waste materials from cotton ginning mills. Its short fiber form increases the physical interweaving density between fibers. Softwood pulp refers to the pulp made from softwood tree species such as pine and fir, which can be specifically prepared by chemical pulp or mechanical pulp. Its long fiber characteristics enhance the tensile strength of the composite fiber. Hardwood pulp refers to the pulp made from hardwood tree species such as eucalyptus and poplar, which can be specifically prepared by the sulfate process. Its wide-width fibers promote the formation of a pore-through structure. Hemp noil refers to the coarse fiber waste generated during the hemp fiber processing process, which can be specifically realized by the residual fibers after degumming. Its surface roughness provides an anchoring site for boron carbide particles.
[0038] Specifically, cotton linter forms a dense interwoven network in cuprammonium solution through short fibers with a length of 0.5 - 3 mm. Softwood pulp constructs an axially reinforced framework in the coagulation bath through long fibers with a length of 2 - 4 mm. Hardwood pulp forms an interlayer pore channel inside the composite fiber through flat fibers with a width of 50 - 100 μm. Hemp noil forms an uneven surface structure through coarse fibers with a diameter of 20 - 50 μm. When boron carbide particles are dispersed in the cellulose matrix, the short fiber network restricts the migration and aggregation of particles, the long fiber framework maintains the overall fiber morphology, the wide-width fiber pores promote the diffusion of water molecules, and the surface structure of the coarse fibers fixes the distribution position of the particles.
[0039] Compared with the prior art, traditional boron-containing fibers use petroleum-based polymers as the matrix, whose raw materials are derived from non-renewable resources and are difficult to degrade, while cotton linter, hemp noil, etc. are all agricultural processing by-products, realizing the recycling of resources; the single fiber structure in the prior art leads to poor air permeability, while the morphological differences of different plant fibers form a multi-scale pore structure inside the composite fiber, and the gas permeability is increased to 1.5 - 2 times that of traditional fibers.
[0040] Through the above technical solutions, the present invention effectively uses renewable plant fibers to replace petroleum-based materials, enabling the composite fiber to be decomposed by soil microorganisms after being discarded; the through pores formed inside the composite fiber make the water vapor transmission rate reach 200 - 300 g / m²·24h, meeting the air permeability requirements of application scenarios such as protective clothing.
[0041] The present invention uses ultrasonic degassing to remove internal bubbles from the boron carbide / cuprammonium pulp mixture, extrudes the spinning solution into the coagulation bath through a micro-injection pump, and controls the boron carbide particle size through multi-stage bath treatment, finally forming a composite fiber with a porous structure and a controllable boron carbide layer thickness.
[0042] Among them, ultrasonic degassing refers to making the tiny bubbles in the mixed slurry break or escape through high-frequency acoustic wave vibration, which can be specifically processed by an ultrasonic generator with a frequency range of 20 - 40 kHz, so as to eliminate the bubble defects inside the spinning solution and avoid structural fracture or uneven dispersion after fiber forming.
[0043] Among them, the micro-injection pump refers to a device that can precisely control the extrusion flow rate of the spinning solution, and specifically, a piston-type injection pump driven by a stepper motor can be used to ensure that the spinning solution forms a continuous and uniform fiber morphology in the coagulation bath.
[0044] Among them, the coagulation bath refers to the liquid-phase medium that promotes the precipitation of cellulose from the cuprammonium solution. Specifically, an aqueous solution mixture of sodium sulfate and sulfuric acid can be used as the coagulant to form a porous fiber structure through rapid phase separation, while fixing the dispersion state of the boron carbide particles.
[0045] Among them, the multi-stage bath treatment refers to a continuous treatment process that sequentially passes through the coagulation bath, the second bath, and the washing bath. Specifically, acid solutions or pure water with different concentrations can be used as the treatment media to remove residual copper ions and stabilize the internal structure of the fiber.
[0046] Among them, the control of the boron carbide particle size refers to limiting the maximum particle size to not exceed 20 microns, and specifically, it can be achieved through mechanical grinding or air classification processes to prevent particle agglomeration and maintain the mechanical strength of the fiber.
[0047] Specifically, the mild dissolution characteristics of the cuprammonium solution for cellulose avoid the use of strong acids and alkalis, reducing the generation of pollutants at the source. The ultrasonic degassing treatment eliminates the bubbles in the mixed slurry, ensuring the uniformity of the spinning solution and avoiding the formation of holes or cracks inside the fiber. The micro-injection pump precisely controls the extrusion amount of the spinning solution, combined with the rapid phase separation effect of the coagulation bath, to form a porous structure running through the fiber axis. This structure not only retains the original air and water permeability of cellulose but also anchors the boron carbide particles through the pores. The strict control of the boron carbide particle size enables it to be fully dispersed in the cellulose matrix, avoiding the decrease in fiber strength caused by particle agglomeration. The multi-stage bath treatment further removes the reaction by-products and simultaneously stabilizes the fiber morphology by gradually adjusting the solution environment.
[0048] Compared with the prior art, the preparation of traditional boron-containing fibers relies on strongly corrosive solvents, such as concentrated sulfuric acid or sodium hydroxide, resulting in the generation of harmful waste liquid during the production process. In contrast, this solution uses a cuprammonium solution system to significantly reduce the risk of chemical pollution. In the prior art, boron carbide is usually directly incorporated into the polymer matrix through mechanical mixing, and the particles are prone to agglomeration to form local accumulations, leading to a decrease in the air permeability of the fiber. In this solution, through the synergistic effect of ultrasonic dispersion and the porous structure, while maintaining the particle dispersion degree, the air and water permeability of the fiber is improved. In addition, traditional boron-containing fibers mostly use synthetic polymers as the matrix and are difficult to degrade naturally, while this solution uses cellulose as the matrix, which can be decomposed by microbial action after use, avoiding environmental pollution.
[0049] Through the above technical solutions, the present invention solves the problem of environmental pollution by chemical reagents in the traditional process, reduces the emission of harmful substances during the production process; through the porous structure design and particle dispersion control, significantly improves the air permeability and water permeability of the composite fiber; utilizes the biodegradable characteristics of the cellulose matrix to avoid the long-term impact of waste fibers on the environment; and at the same time realizes the uniform dispersion of boron carbide particles inside the fiber to ensure the stability of the neutron shielding performance. Example 1
[0050] (1) 20 mL of cuprammonium solution (Cu 1 mol / L) and 4 g of plant fiber were mixed, 5% citric acid with respect to the mass fraction of copper ions was added, and stirred to fully dissolve the solid. It was filtered through a polypropylene filter screen with an average pore size of about 1 - 20 um to obtain cuprammonium pulp; 0.45 g of 1000 nm boron carbide powder was added to the cuprammonium pulp, and fully mixed to form a boron carbide / cuprammonium pulp mixture; ultrasonic degassing was carried out for 20 min to remove internal bubbles as much as possible, and a boron carbide / cellulose spinning solution was obtained. (2) The spinning solution was added to a micro-injection pump, the injection pump was started, and the spinning solution was extruded through a spinneret into a coagulation bath, and quickly drawn and solidified; the fiber was collected after passing through a 20% sodium hydroxide coagulation bath, a 3% sulfuric acid second bath, and a washing bath. After oiling, drying and finishing, boron carbide / cellulose composite fiber (boron carbide content ≈ 0.1 (w / w)) was prepared. The fiber breaking strength was 1.5 cN / dtex. Example 2
[0051] (1) 20 mL of cuprammonium solution (Cu 1 mol / L) and 4 g of plant fiber were mixed, 5% citric acid with respect to the mass fraction of copper ions was added, and stirred to fully dissolve the solid. It was filtered through a polypropylene filter screen with an average pore size of about 1 - 20 um to obtain cuprammonium pulp; 1.72 g of 1000 nm boron carbide powder was added to the cuprammonium pulp, and fully mixed to form a boron carbide / cuprammonium pulp mixture; ultrasonic degassing was carried out for 20 min to remove internal bubbles as much as possible, and a boron carbide / cellulose spinning solution was obtained. (2) The spinning solution was added to a micro-injection pump, the injection pump was started, and the spinning solution was extruded through a spinneret into a coagulation bath, and quickly drawn and solidified; the fiber was collected after passing through a 20% sodium hydroxide coagulation bath, a 3% sulfuric acid second bath, and a washing bath. After oiling, drying and finishing, boron carbide / cellulose composite fiber (boron carbide content ≈ 0.3 (w / w)) was prepared. The fiber breaking strength was 0.98 cN / dtex. Example 3
[0052] (1) 500 mL of copper ammonia solution (Cu 1 mol / L) and 100 g of plant fiber were mixed, and citric acid with a copper ion mass fraction of 5% was added. The mixture was stirred to fully dissolve the solid, and then filtered through a polypropylene filter with an average pore size of about 1 - 20 μm to obtain copper ammonia pulp. The pulp was evenly divided into 5 equal - mass portions, and 0 g, 2.90 g, 5.75 g, 8.60 g, 11.50 g, 14.35 g of boron carbide powder with a particle size of 500 nm were added to each portion respectively and mixed thoroughly to form boron carbide / copper ammonia pulp mixtures. Ultrasonic degassing was carried out for 20 min to remove internal bubbles as much as possible, obtaining boron carbide / cellulose spinning solution. (2) The spinning solution was added to a micro - injection pump. The injection pump was turned on, and the spinning solution was extruded through a spinneret into a coagulation bath, and quickly drawn and solidified. The fibers were wound after passing through a 20% sodium hydroxide coagulation bath, a 3% sulfuric acid second bath, and a washing bath. After oiling, drying, and finishing, boron carbide / cellulose composite fibers were obtained.
[0053] The breaking strength of the obtained boron carbide / cellulose composite fibers is shown in Table 1: Table 1 Breaking strength of boron carbide / cellulose composite fibers
[0054] SEM, EDS, and XRD characterizations proved that the regenerated cellulose fibers and boron carbide particles were closely combined and evenly distributed, and boron carbide was embedded in the substrate of regenerated cellulose in a physical mixing manner ( Figures 2 to 4 ). Only a small amount of particles were recovered in the coagulation bath, and almost all boron carbide particles were combined with cellulose during the regeneration process to form the composite material. Using copper ethylenediamine solution as a solvent to prepare copper ammonia pulp had the same effect as using copper ammonia solution. The strength of boron carbide / cellulose composite fibers can be further improved by means such as compounding and chemical strengthening.
[0055] Through the above - mentioned technical solutions, the present invention solves the problem of environmental pollution by chemical reagents in traditional processes, reduces the use and residue of harmful substances; by controlling the pore structure of the fiber matrix and the distribution pattern of boron carbide, the air permeability and water permeability are improved while maintaining the mechanical properties of the fibers; by utilizing the mild reaction conditions of the copper ammonia method and the biodegradable characteristics of plant fibers, the synergetic optimization of environmental protection and functionality is achieved.
[0056] The above description is only for the embodiments of the present invention and is not intended to limit the protection scope of the present invention. For those skilled in the art, the present invention can have various modifications and changes. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.
Claims
1. A boron carbide / regenerated cellulose composite fiber prepared based on the cuprammonia method, characterized in that: The boron carbide / regenerated cellulose composite fiber is mainly composed of regenerated cellulose and boron carbide, and the cellulose and boron carbide particles are closely interwoven.
2. A method for processing boron carbide / regenerated cellulose composite fibers prepared by the cuprammonia method as claimed in claim 1, characterized in that It is made by the copper ammonia method, which includes the following steps: (1) A copper ammonia solution or a copper ethylenediamine solution and plant fibers are mixed at a copper element / cellulose mass ratio of 0.2 to 0.4, stirred to fully dissolve the solid, added with citric acid having a copper ion mass fraction of 5%, and filtered with a polypropylene filter having an average pore size of about 1 to 20 um to obtain a copper ammonia pulp; boron carbide powder is added to the copper ammonia pulp and fully mixed to form a boron carbide / copper ammonia pulp mixture; ultrasonic degassing is used to remove internal bubbles as much as possible to obtain a boron carbide / cellulose spinning solution; (2) The spinning solution is added to the micro-injection pump, and the injection pump is turned on. The spinning solution is extruded into the coagulation bath through the spinneret, and is quickly drawn and coagulated into a fiber. The fiber passes through the coagulation bath, the second bath, and the washing bath, and then is collected. After oiling, drying, and finishing, the boron carbide / cellulose composite fiber is obtained.
3. The method for processing boron carbide / regenerated cellulose composite fibers prepared by the cuprammonia method according to claim 2, characterized in that: The particle size of the boron carbide powder is ≤20 μm, preferably in the range of 2 to 0.5 μm.
4. The method for processing boron carbide / regenerated cellulose composite fibers prepared by the cuprammonia method according to claim 2, characterized in that: The plant fibers include but are not limited to cotton linters, softwood pulp, hardwood pulp and hemp noil.
5. The method for processing boron carbide / regenerated cellulose composite fibers prepared by the cuprammonia method according to claim 2, characterized in that: The ultrasonic degassing is carried out using an ultrasonic generator with a frequency range of 20 to 40 kHz, and the processing time is not less than 10 minutes.
6. The method for processing boron carbide / regenerated cellulose composite fibers prepared by the cuprammonia method according to claim 2, characterized in that: The concentration of copper element in the copper ammonia solution is 0.5-2 mol / L.